KAPITALISME EKONOMI SYARIAH (IAIN Tulungagung, 2014)
Differences of Islamic economic system and capitalist economic system are not only its application but also philosophy. Above this different philosophy is structured target, different principles and norm. This matter because confidence of someone influence the way of approach in forming personality, behavioral, life style, and human being appetite. In broader context, confidence also influence attitude to others, resource, and environment. In capitalist system, God is retired. This Matter is reflected in concept “faire laissez” and “invisible hand”. Through this philosophy, we can consider the target of capitalist economics only merely its growth for individual satisfaction. Islamic economic philosophy in general can be seen from al-Muthaffifin (1- 6). Allah said: 1) Woe to those who cheat. 2) (Namely) those who, when receiving the dose of other people they ask fulfilled. 3) And when they measure or weigh for others, they reduce. 4) It is not the people think that they will be resurrected Indeed. 5) On a great day. 6) (ie) the day (when) people are standing facing the Lord of the Worlds. But in its development has occurred mixing of two different systems. Islamic Economics is clearly differently from capitalist economy actually mixed the mortar in order to gain the maximum profit.Keywords: Capitalism, Islamic Economic